Ethno-medico-botanical knowledge from Kaukhali proper and Betbunia of Rangamati District - Yusuf, Mohammed; Wahab, Md Abdul; Chowdhury, Jasim Uddin; Begum, Jaripa (Bangladesh Journal of Plant Taxonomy, 2006)
A survey was carried out between July 2001 and June 2002 in Kaukhali proper and Betbunia area of Rangamati district to document the medicinal plants of that area and their uses. During this work 34 species representing 23 genera and 17 families were found, which are used by the Chakma and Marma tribes and the Bangalis living there for the treatment of 31 diseases. Botanical and tribal names of the plants, parts used, name of the diseases, and name of the users have been mentioned. Key words: Ethno-medico-botany, Kaukhali, Betbunia, Rangamati DOI: 10.3329/bjpt.v13i1.594 Bangladesh J. Plant Taxon. 13(1): 55-61, 2006 (June)